Diversity of Adult Trees in Two Different Forest Types of Tropical Forest of District Balaghat Madhya Pradesh (International Journal of Food and Nutritional Sciences, 2022)
A study was conducted to analyze the phytosociological structure of two types of Tropical Forest of district Balaghat, Madhya Pradesh viz. Sal Forest (SF) and Teak Forest (TF). The objective of the current study was to understand the diversity of adult trees present in that forest along with their stem density per hectare, basal area per hectare and Importance Value Index. In the present study 12 plots of 50 x 50 m was laid down in each forest type and it was further divided into 25 sub plots of 10 x 10 m and individual trees having ≥ 10 DBH (Diameter at Breast Hight) were recorded and ecological parameters are studied. A total of 50 Angiosperm species belong to 41 Genera and 24 Families was recorded during this study.